Joslin diabetes manual - Krall, Leo P; Beaser, Richard S (Lea & Febiger, 1989)
Joslin Diabetes Center, Boston, Massachusetts. Manual for patient education. DNLM: 1. Diabetes Mellitus - popular works.
Keywords: diabetická dieta; vnitřní lékařství; Pregnancy in Diabetics; diabetes mellitus; Diabetes Mellitus; těhotenství při diabetu; komplikace diabetu; inzulin; Insulin; endokrinologie; hyperglykemie; Hyperglycemia; Diabetes Complications; Diet, Diabetic